Shaping future-ready graduates with mindset shifts: studying the impact of integrating critical and design thinking in design innovation education - Patel, Nadya Shaznay; Puah, Shermain; Kok, Xiao-Feng Kenan (Frontiers in Education, 2024)
In an era marked by rapid change and complex global challenges, Institutes of Higher Learning (IHLs) are tasked with preparing students to navigate and address these evolving demands. This paper explores the critical role of Higher Education (HE) in equipping students with the necessary skills and mindsets to tackle real-world problems through innovative solutions. Integrating critical thinking and design thinking within a Design Innovation module is central to this exploration. The study is undergirded by a conceptual framework that blends critical, design, and futures thinking, focusing exclusively in this paper on applying critical thinking (CT) and design thinking (DT). The research investigates two primary questions: (1) How do students' DT and CT mindsets change after participation in a Design Innovation module? (2) Is CT a prerequisite for developing DT? This study aims to illuminate the shifts in students' mindsets from before to after the completion of the module, highlighting the importance of developing key dispositions for ethical and socially responsible problem-solving. Results show a statistically significant increase in CT and DT disposition scores from pre-to post-test, suggesting a shift to more positive CT and DT mindsets after going through the Design Innovation module. In addition, a significant moderation effect of pre-test CT mindset on the relationship between pre-test and post-test DT mindset scores was observed, implying that CT was a prerequisite for DT. The findings offer insights into the module's effectiveness in fostering future-ready graduates' thinking capabilities on innovating for real-world challenges and highlight the need for our future-ready students to achieve critical competence and creative confidence. Finally, we conclude the paper with recommendations for educators to integrate CT skill development intentionally and in tandem with DT skill development for a balanced approach to developing critical competence and creative confidence in interdisciplinary courses.